Systematic Literature Review: The Influence Of Tax Understanding, Taxpayer Awareness, And Tax Socialization On Tax Compliance Of Msmes In Indonesia - Lestari, Desak Nyoman Lia; Fuadah, Luk Luk (Journal of Management, Economic, and Accounting, 2025)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) plays a crucial role in increasing state revenue and supporting national development. However, the level of tax compliance among MSMEs in Indonesia is still relatively low, influenced by various factors such as tax understanding, taxpayer awareness, and the effectiveness of tax socialization. This study aims to analyze the impact of tax understanding, taxpayer awareness, and tax socialization on MSME tax compliance in Indonesia through a Systematic Literature Review (SLR) approach. The research method involved collecting literature from four main databases (Emerald Insight, DOAJ, Google Scholar, and ResearchGate), resulting in 331 articles. After screening, 21 relevant articles were selected for analysis. The results show that good tax understanding positively contributes to increased tax compliance, while high taxpayer awareness and effective tax socialization also play a significant role in influencing compliance behavior. Tax education-based policies, both technical and value-based, prove to be key in enhancing MSME tax compliance, especially in more difficult-to-reach areas. This study provides important contributions to tax policies that are more responsive to the characteristics of MSMEs in Indonesia.